Features of the formate dehydrogenase mRNA necessary for decoding of the UGA codon as selenocysteine. - Zinoni, F (1990)
The fdhF gene encoding the 80-kDa selenopolypeptide subunit of formate dehydrogenase H from Escherichia coli contains an in-frame TGA codon at amino acid position 140, which encodes selenocysteine. We have analyzed how this UGA "sense codon" is discriminated from a UGA codon signaling polypeptide chain termination. Deletions were introduced from the 3' side into the fdhF gene and the truncated 5' segments were fused in-frame to the lacZ reporter gene. Efficient read-through of the UGA codon, as measured by beta-galactosidase activity and incorporation of selenium, was dependent on the presence of at least 40 bases of fdhF mRNA downstream of the UGA codon. There was excellent correlation between the results of the deletion studies and the existence of a putative stem-loop structure lying immediately downstream of the UGA in that deletions extending into the helix drastically reduced UGA translation. Similar secondary structures can be formed in the mRNAs coding for other selenoproteins. Selenocysteine insertion cartridges were synthesized that contained this hairpin structure and variable portions of the fdhF gene upstream of the UGA codon and inserted into the lacZ gene. Expression studies showed that upstream sequences were not required for selenocysteine insertion but that they may be involved in modulating the efficiency of read-through. Translation of the UGA codon was found to occur with high fidelity since it was refractory to ribosomal mutations affecting proofreading and to suppression by the sup-9 gene product.